On the Drivers of Inflation in Sub-Saharan Africa - Nguyen, Anh (IMF Working Papers; Working Paper ;, 2015)
The perception that inflation dynamics in Sub-Saharan Africa (SSA) are driven by supply shocks implies a limited role for monetary policy in influencing inflation in the short run. SSA's rapid growth, its integration with the global economy, changes in the policy frameworks, among others, in the last decade suggest that the drivers of inflation may have changed. We quantitatively analyze inflation dynamics in SSA using a Global VAR model, which incorporates trade and financial linkages among economies, as well as the role of regional and global demand and inflationary spillovers. We find that in the past 25 years, the main drivers of inflation have been domestic supply shocks and shocks to exchange rate and monetary variables; but that, in recent years, the contribution of these shocks to inflation has fallen. Domestic demand pressures as well as global shocks, and particularly shocks to output, however, have played a larger role in driving inflation over the last decade. We also show that country characteristics matter-the extent of oil and food imports, vulnerability to weather shocks, economic importance of agriculture, trade openness and policy regime, among others, help in explaining the role of shocks.